Question
Find the derivative of the function. \[ y=x^{-7}+x^{-6}-6 \] \( y^{\prime}(x)=\square \)
Ask by Clarke Kelley. in the United States
Feb 03,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
The derivative of the function \( y = x^{-7} + x^{-6} - 6 \) is \( y^{\prime}(x) = -7x^{-8} - 6x^{-7} \).
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Unlock
Reviewed and approved by the UpStudy tutoring team
Like
Mind Expander
To find the derivative of the function \( y = x^{-7} + x^{-6} - 6 \), we apply the power rule. The derivative of \( x^n \) is \( nx^{n-1} \). For the term \( x^{-7} \), the derivative is \( -7x^{-8} \). For \( x^{-6} \), the derivative is \( -6x^{-7} \). The derivative of a constant, like \(-6\), is \(0\). So, the derivative is: \[ y' = -7x^{-8} - 6x^{-7} \] Thus, \( y'(x) = -7x^{-8} - 6x^{-7} \).